Elevated Levels of Apolipoprotein CIII Increase the Risk of Postprandial Hypertriglyceridemia - Guan, Yunpeng; Hou, Xiaoyu; Tian, Peipei; Ren, Luping; Tang, Yong; Song, An; Zhao, Jiajun; Gao, Ling; Song, Guangyao (Frontiers in Endocrinology, 2021)
Background To investigate possible mechanisms of postprandial hypertriglyceridemia (PPT), we analyzed serum lipid and apolipoprotein (Apo) AⅠ, B, CⅡ and CⅢ levels before and after a high-fat meal. Methods The study has been registered with the China Clinical Trial Registry (registration number:ChiCTR1800019514; URL:http://www.chictr.org.cn/index.aspx). We recruited 143 volunteers with normal fasting triglyceride (TG) levels. All subjects consumed a high-fat test meal. Venous blood samples were obtained during fasting and at 2, 4, and 6 hours after the high-fat meal. PPT was defined as TG ≥2.5 mmol/L any time after the meal. Subjects were divided into two groups according to the high-fat meal test results: postprandial normal triglyceride (PNT) and PPT. We compared the fasting and postprandial lipid and ApoAⅠ, ApoB, ApoCⅡ and ApoCⅢ levels between the two groups. Results Significant differences were found between the groups in fasting insulin, homeostasis model assessment of insulin resistance (HOMA-IR), TG, total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), non-high-density lipoprotein cholesterol (non-HDL-C), TG-rich lipoprotein remnants (TRLRs), ApoB, ApoCⅢ, ApoAⅠ/ApoB and ApoCⅡ/ApoCⅢ. The insulin, HOMA-IR, TG, TC, LDL-C, non-HDL-C, TRLRs, ApoB, ApoCⅢ and ApoCⅡ/ApoCⅢ values were higher in the PPT group, while the ApoAⅠ/ApoB ratio was higher in the PNT group. The postprandial TG level peaked in the PNT group 2 hours after the meal but was significantly higher in the PPT group and peaked at 4 hours. TRLRs gradually increased within 6 hours after the high-fat meal in both groups. The area under the curve (AUC) of TG and TRLRs and the AUC increment were higher in the PPT group (P<0.001). ApoCⅢ peaked in the PNT group 2 hours after the meal and gradually decreased. ApoCⅢ gradually increased in the PPT group within 6 hours after the meal, exhibiting a greater AUC increment (P<0.001). Fasting ApoCⅢ was positively correlated with age, systolic and diastolic blood pressure, body mass index (BMI), waist circumference, TC, TG, LDL-C, non-HDL-C, TRLRs, and ApoB (P<0.05). ApoCⅢ was an independent risk factor of PPT after adjustment for BMI, waist circumference, TC, LDL-C, and ApoB (P<0.001, OR=1.188). Conclusions Elevated ApoCⅢ levels may cause PPT.